Earmarked funding for multilateral development cooperation: Asset and impediment - Max-Otto Baumann; Erik Lundsgaarde; Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
Multilateral cooperation means that states can collectively achieve more than they can through individual and bilateral efforts alone. Multilateral organisations are important instruments for this: they have a greater geographic and thematic reach, operate at a larger scale and stand for multilateral norms and values. Funding provides an important basis for multilateral development cooperation - only with sufficient core funding at their disposal can multilaterals effectively and independently perform the functions member states expect. This includes a problem-driven allocation of resources, strategic orientation, and flexibility in the implementation of and advocacy for internationally agreed values, norms and standards. The coronavirus (COVID-19) pandemic has demonstrated the need for international cooperation to deal with multiple crises that affect all societies. It has also proved the value of multilateral organisations that can combat the spread of COVID-19 worldwide and support countries where health systems are weakest. Over the last three decades, the funding trend for multilateral organisations has been towards ever greater shares of earmarked funding, whereas core funding has grown much more slowly or has even declined for some organisations. A contribution is earmarked when a contributor directs it to a specific pooled fund, programme or - most typically - a project in a specific country. The substantial increase in such earmarked (also 'restricted', 'bi-multi') funding has certainly buoyed organisations and helped to close many funding gaps. However, such atomised funding practices come with the risk of instrumentalising multilateral organisations for project implementation purposes, and by doing so, reducing their programmatic coherence, effectiveness, efficiency and legitimacy. For contributors, earmarking has often been a politically convenient choice. It provides them with control over the use of their resources and visibility for results achieved, all at attractively low implementation costs. However, both the direct implications of earmarking for specific interventions and the more systemic effects on the effectiveness and efficiency of the multilateral organisations tend to be overlooked. At the scale we see it today, earmarking may actually undermine the ability of multilaterals to fulfil the member states' expectations and make full use of their unique assets to advance the 2030 Agenda for Sustainable Development. To fully harness the potential of multilateral development cooperation, both member states and multilateral organisations have to change course. * A larger number of contributors - also beyond the Organisation for Economic Co-operation and Development/Development Assistance Committee (OECD/DAC) - should contribute additional funds to the multilateral development system. * Contributors should reverse the trend of growing shares of earmarked funding by increasing core funds across organisations. * Contributors should use earmarked funding more prudently to support rather than undermine multilateral functions. Multi-donor pooled funds are a viable alternative. * Multilaterals should invest in transparent institutional mechanisms that provide checks for resource mobilisation.
Keywords: 330